Types of Lens Structure in Intumescent Cataract - E. S. Pirogova; O. L. Fabrikantov; S. I. Nikolashin (Oftalʹmologiâ)
Purpose: to study the structure of the swelling lens, the dependence of its anatomical parameters on the nucleus sizes and density, patients’ age.Patients and methods. 52 patients with intumescent mature cataract were examined. All patients underwent phacoemulsification with a two-stage continuous circular capsulorhexis. After the 2–2.5 mm capsulorhexis had been created, the liquid lenticular masses were removed from the anterior and posterior lens compartment with the aspiration/irrigation system. Visually we determined the size of the nucleus, its color and density according to Buratto’s classification.Results. When performing this work 4 types of the swelling lens structure were revealed. Type I — a small emerging white nucleus with large amount of liquid lenticular masses in the anterior and posterior lens compartment, II degree of density according to Buratto’s classification. The mean age was 49.09 ± 3.19 years old. The related ophthalmic diseases accounted for 36.4%. Type II — a large white nucleus with the presence of liquefied lenticular masses in the anterior and posterior lens compartment. III degree of density according to Buratto’s classification. The mean age was 71.00 ± 1.92 years old. Associated diseases — 84.6%. Type III — a large brown nucleus with the presence of liquefied lenticular masses in the anterior and posterior lens compartment. IV degree of density according to Buratto’s classification. The mean age was 75.84 ± 1.46 years old. Associated diseases — 100%. Type IV — a small, very dense, brown nucleus with liquid lenticular masses. V degree of density according to Buratto’s classification. The mean age was 77.33 ± 2.49 years old. Associated diseases — 100%.Conclusion. 4 types of lens structure in intumescent cataract were described depending on the nucleus size, density, the amount of the lenticular masses. By means of UBM method, it was shown that intumescent cataract is accompanied with the alterations of the ocular anterior segment parameters, which depend on the type of lens structure. It was revealed that the types of swelling lens structure are directly connected to the patients’ age: mean age of patients with type I — 49.09 ± 3.19 years old, with type II — 71.00 ± 1.92, with type III — 75.84 ± 1.46, with type IV — 77.33 ± 2.49 years old.